RNA-seq and In Vitro Experiments Reveal the Protective Effect of Curcumin against 5-Fluorouracil-Induced Intestinal Mucositis via IL-6/STAT3 Signaling Pathway - Xuan-ying Wang; Bo Zhang; Yi Lu; Lu Xu; Yi-jie Wang; Bi-yu Cai; Qing-hua Yao (Journal of Immunology Research)
Although first-line chemotherapy drugs, including 5-fluorouracil (5-FU), remain one of the major choice for cancer treatment, the clinical use is also accompanied with dose-depending toxicities, such as intestinal mucositis (IM), in cancer patients undergoing treatment. IM-induced gastrointestinal adverse reactions become frequent reason to postpone chemotherapy and have negative impacts on therapeutic outcomes and prognosis. Various studies have evidenced the anticancer role of curcumin in many cancers; except for this effect, studies also indicated a protective role of curcumin in intestinal diseases. Therefore, in this study, we investigated the effect of curcumin on inflammation, intestinal epithelial cell damage in an IM model. 5-FU was used to induce the model of IM in intestinal epithelial cells, and curcumin at different concentrations was administrated. The results showed that curcumin efficiently attenuated 5-FU-induced damage to IEC-6 cells, inhibited the levels of inflammatory cytokines, attenuated the 5-FU-induced inhibition on cell viability, and displayed antiapoptosis effect on IEC-6 cells. Further RNA-sequencing analysis and experiment validation found that curcumin displays its protective effect against 5-FU-induced IM in intestinal epithelial cells by the inhibition of IL-6/STAT3 signaling pathway. Taken together, these findings suggested that curcumin may be provided as a therapeutic agent in prevention and treatment of chemotherapy-induced IM.